Webinar career talk: finding passion and resilience - Rizky Yudaruddin; Karina Kausalya Laman; Kharisma Ambarsari; Putri Zhafira Chairunnisa; Silvitri Diah Yulianti (Faculty of Economics and Business Mulawarman University, 2022)
Passion is defined as an affective structure, an optimistic orientation toward work that both produces and gives meaning to a variety of emotional dispositions, whereas The Oxford English Dictionary defines the contemporary use of passion as